Diagnostic utility of droplet digital PCR for HIV reservoir quantification - Wim Trypsteen; Maja Kiselinova; Linos Vandekerckhove; Ward De Spiegelaere (Elsevier, 2016)
Quantitative real-time PCR (qPCR) is implemented in many molecular laboratories worldwide for the quantification of viral nucleic acids. However, over the last two decades, there has been renewed interest in the concept of digital PCR (dPCR) as this platform offers direct quantification without the need for standard curves, a simplified workflow and the possibility to extend the current detection limit. These benefits are of great interest in terms of the quantification of low viral levels in HIV reservoir research because changes in the dynamics of residual HIV reservoirs will be important to monitor HIV cure efforts.Here, we have implemented a systematic literature screening and text mining approach to map the use of droplet dPCR (ddPCR) in the context of HIV quantification. In addition, several technical aspects of ddPCR were compared with qPCR: accuracy, sensitivity, precision and reproducibility, to determine its diagnostic utility.We have observed that ddPCR was used in different body compartments in multiple HIV-1 and HIV-2 assays, with the majority of reported assays focusing on HIV-1 DNA-based applications (i.e. total HIV DNA). Furthermore, ddPCR showed a higher accuracy, precision and reproducibility, but similar sensitivity when compared to qPCR due to reported false positive droplets in the negative template controls with a need for standardised data analysis (i.e. threshold determination).In the context of a low level of detection and HIV reservoir diagnostics, ddPCR can offer a valid alternative to qPCR-based assays but before this platform can be clinically accredited, some remaining issues need to be resolved.